Prevalence and associated factors of foot ulcer among diabetic patients in Ethiopia: a systematic review and meta-analysis - Tadesse Tolossa; Belayneh Mengist; Diriba Mulisa; Getahun Fetensa; Ebisa Turi; Amanuel Abajobir (BMC, 2020)
Abstract Background Diabetes and its complications including foot ulcer constitute a global public health challenge attributing to a significant cause of morbidity and mortality. Foot ulcer is one of the long-term complication of diabetes mellitus which lead to infection and amputation of lower extremities. In Ethiopia, findings from few studies were inconsistent and there is a need to systematically pool existing data to determine the magnitude of foot ulcer in diabetics and factors contributing to it. Methods We identified articles through electronic databases such as Medline, Hinari, Pub Med, Cochrane library, the Web of Science and Google Scholar. Accordingly, we identified 95 published and one unpublished article. Finally, eleven studies which fullfilled eligibility criteria were included in final systematic review and meta-analysis. Data were extracted using a standardized data extraction checklist and the analyses were conducted using STATA version 14. The Cochrane Q test statistic and I 2 tests were used to assess heterogeneity. Results The overall magnitude of foot ulcer was 12.98% (95%CI: 7.81-18.15) in diabetic patients in Ethiopia. Sub-group analyses revealed highest prevalence in Addis Ababa (19.31% (95%CI: 2.7. 41.37)). Foot ulcer was significantly associated with rural residence (OR = 2.72, 95%, CI: 1.84-4.01)), presence of callus on the feet ((OR = 12.67, 95%, CI: 6.47-24.79)), a body mass index of ≥24.5 ((OR = 2.68, 95%, CI: 1.58-4.56)), poor self- care practice ((OR = 1.47, 95%CI: 1.25-1.73)), type I diabetes mellitus ((OR = 0.42, 95%, CI: 0.22-0.79)), staying with DM for < 10 years ((OR = 0.23, 95%, CI: 0.11-0.50)), and age < 45 years ((OR = 0.44, 95%, CI: 0.21-0.92)). Conclusion The prevalence of diabetic foot ulcers in Ethiopia is relatively low, although its trend is increasing from time to time. Socio-demographic factors, body weight, and healthcare practice contribute to the development of diabetic foot ulcers. Appropriate interventions towards patient self-care practice, lifestyle modification and follow-up are wanted to prevent diabetic foot ulcers.